Barriers to nutritional pregnancy preparation and support needs in women and men: Qualitative study based on the Theoretical Domains Framework. (August 2021) - Quayyum, Fareeha; Dombrowski, Stephan U
Purpose: Eating behaviours prior to conception may impact the health of the offspring at birth and throughout life. Women and men of childbearing age often follow a nutritionally poor preconception diet. Nutritional support before pregnancy has the potential to improve the health of future offspring. This study examined barriers to nutritional preparation for pregnancy and perceived support needs of women and men of childbearing age. Design: Qualitative interviews based on the Theoretical Domains Framework. Setting: Online. Participants: Eligible individuals were (1) New Brunswick residents (all genders), (2) over 19 years old, and (3) intended to have offspring in the future. Methods: Interviews were conducted via online instant messenger and analysed thematically. Results: Interviews of participants (n = 19, age = 19–23 years, 14 women, 5 men) gave rise to five key theoretical domains: lack of knowledge; lack of beliefs about capabilities; suboptimal environmental context and resources; unfavourable social influences; and restrictive social roles. Suggestions to address pregnancy preparation support needs included healthcare professional consultations; accessible and credible references; increasing access to healthy food; proactive engagement; and gender-specific support. Conclusion: Women and men called for various types of preconception support to address identified barriers, ranging from healthcare professional advice and credible informational resources to broader interventions such as making healthy food more affordable and normalizing discussion of preconception health throughout the life course.